PENGARUH INOKULASI MIKORIZA ARBUSKULAR TERHADAP PERTUMBUHAN BIBIIT DAN INTENSITAS PENYAKIT BERCAK DAUN CENGKEH - Ayu Octavia Tanjung Putri; Bambang Hadisutrisno; Arif Wibowo (Jurnal Pemuliaan Tanaman Hutan, 2016)
The potential of arbuscular mycorrhiza fungi on the growth of clove seedling and leaf spot intensity. This researches aims to assess the ability of arbuscular mycorrhiza (AM) fungi in growth and suppress the intensity of leaf spot disease on clove seeds. The experiment was arraged in completely randomized design (CRD) 2 x 2 factorial. The treatments examined were: without mycorrhiza and compost (M0P0), without mycorrhiza and with compost (M0P1), with mycorrhiza and without compost (M1P0), and with mycorrhiza and compost (M1P1). The observed variables were the clove seedlings height, leaf numbers, symptom and intensity of leaf spot disease, and detection of salicylic acid (SA) with thin layer chromatography (TLC). The result showed that aplication of AM Fungi (M1) to clove seedlings support clove growth and dicreased intensity of leaf spot disease, but there was no interaction between mycorrhiza and composting in all observation variables. Salicylic acid contained in all treatment were tested.